Repeated practice runs during on-snow training do not generate any measurable neuromuscular alterations in elite alpine skiers - Alhammoud, Marine; Girard, Olivier; Hansen, Clint; Racinais, Sébastien; Meyer, Frédéric; Hautier, Christophe André; Morel, Baptiste (Frontiers in Sports and Active Living, 2022)
Background Alpine skiers typically train using repeated practice runs requiring high bursts of muscle activity but there is little field-based evidence characterizing neuromuscular function across successive runs. Purpose To examine the impact of repeated ski runs on electromyographic activity (EMG) of the knee extensors and flexors in elite alpine skiers. Methods Nineteen national team alpine skiers were tested during regular ski training [Slalom (SL), Giant Slalom (GS), Super Giant Slalom and Downhill (Speed)] for a total of 39 training sessions. The surface EMG of the vastus lateralis (VL), rectus femoris (RF), vastus medialis (VM), biceps femoris (BF) and semimembranosus/semitendinosus (SMST) muscles was continuously recorded along with right knee and hip angles. The EMG root mean square signal was normalized to a maximal voluntary contraction (%MVC). The first and fourth runs of the training session were compared. Results There was no meaningful main effect of run on EMG relative activation time or mean power frequency beyond the skier's intrinsic variability. However, EMG activity of the vastii increased from the first to the fourth run in SL [VM, ~+3%MVC for IL and outside leg (OL), p = 0.035)], speed (VL, IL:+6%/OL:+11%, p = 0.015), and GS (VM, IL:0/OL:+7%, p < 0.001); the later with an interaction with leg (p < 0.001) due to a localized increase on the OL. The run time and turn time did not change from the first to the fourth run. There were no meaningful changes in angular velocities, amplitude of movement, or maximal and minimal angles. Conclusion Neuromuscular activity remains highly stable in elite skiers with low variability across four runs.